The French Revolution and Napoleon : a sourcebook - Dwyer, Philip G.; McPhee, Peter, 1948- (Routledge, 2002)
The upheavals, terror, and drama of the French Revolutionary and Napoleonic period restructured politics and society on a grand scale, making this the defining moment for modern European history. This volume collects together a wide selection of primary texts to explain the process behind the enormous changes undergone by France and Europe between 1787 and 1815, from the Terror to the Counter-Revolution and from Marie-Antoinette to Robespierre and Bonaparte. While bringing the impact of historical events to life, Philip Dwyer and Peter McPhee provide a clear outline of the period through key documents and lucid introductory passages and commentary. They illustrate the meaning of the Revolution for peasants, sans-culottes, women, and slaves, as well as placing events within a wider European context. Students will find this an invaluable source of information on the Revolution as a whole as well as the international significance of the events.